Hubungan Antara Persepsi dan Tingkat Kesadaran Siswa SMAN 02 Wonogiri dalam Menghadapi Bencana Klimatologis - Ajeng Santika Putri; Trifia Safira Ristiani; Unsa Laini Rahmawati; Siti Azizah Susilawati (Universitas Syiah Kuala, Banda Aceh, 2025)
This study was conducted to analyze the relationship between perception and level of awareness of students of SMAN 02 Wonogiri in facing climatological disasters. This study uses a quantitative approach with an associative method. Data were collected through a survey using a questionnaire filled out by 251 students selected through a purposive sampling technique. The variables in the study include student perception and level of awareness. According to Arum Ariningtyas, indicators of student perception include knowledge, understanding, and application and indicators of student awareness include knowledge, attitudes, and actions. The data analysis technique was carried out using the Spearman Rank correlation test to determine the relationship between perception and level of awareness. The results of this study indicate a weak positive relationship between